Early Superhumps in the "King of the Superoutbursts" System WZ Sge - Andronov, I. L.; Yushchenko, A. V.; Niarchos, P. G.; Gazeas, K. (Odessa Astronomical Publications, 2001)
Time series analysis of 6 nights of CCD observations of WZ Sge after it's unexpected superoutburst on July 23, 2001 has shown highly asymmetric periodic variations with a period 0.0566513(22)deg, full amplitude 0.218(4)m and a very high asymmetry M-m=0.670(9), a secondary minimum 0.38P after the main one. The initial epochs are Tmax=BJD 2452118.7483(3) and Tmin=BJD 52118.7670(2). The characteristics of the phase light curve are listed. In addition, we have found superhumps with a semi-amplitude of 0.021(2)m and an ephemeris Tmax,sh=BJD 2452117.6830(8)+0.057435(45)d E. Other peaks at 21 and 25 minutes possibly correspond to quasi-periodic oscillations with an effective semi-amplitude of 0.014m.
Keywords: DWARF NOVAE: SUPERHUMPS: WZ SGE; STARS: VARIABLE: CATACLYSMIC